Loss of spin polarization in ferromagnet/ferroelectric tunnel junctions due to screening effects. (26th October 2018) - Sen, C; Aldulaimi, W A S; Mohammadmoradi, O; Misirlioglu, I B
Abstract: Electric field control of magnetization allows further miniaturization of integrated circuits for binary bit processing and data storage as it eliminates the need for bulky sophisticated systems to induce magnetic fields. Magnetoelectric coupling inherent to the bulk of multiferroic films or control of spin orientation in magnetic layers via piezoelectric strain in dual component composites have been two approaches standing out. Another magnetoelectric effect is spin-dependent screening that occurs at dielectric/ferromagnet interfaces which is of great importance for spin selective tunnel junctions. Here, we analyze the spin-dependent screening of ferroelectric polarization in a film interfacing ferromagnetic electrodes using the continuity equations in continuum media. The competition between the electrostatic and the magnetochemical potential in the FM electrodes gives rise to a reduction in the net magnetic moment near the interface due to spin mixing, extending to a distance comparable to the Thomas–Fermi screening length. Our continuum media treatment shows that the local spin population in spin subbands near the interfaces can dramatically deviate from bulk, which is in qualitative agreement with recent first principles results. We compute the tunneling currents for the majority and minority spins using the Wentzel–Kramers–Brillouin approximation as a function of ferroelectric polarization. We find that the spin polarization tends to disappear for increasing values of ferroelectric polarization in direct connection with the increase in subband spin population for minority spins at the interface.